Moving for Good: Educational Gains from Leaving Violence Behind - María Padilla-Romo; Cecilia Peluffo (Institute of Labor Economics (IZA), 2025)
This paper estimates the effects of moving away from violent environments into safer areas on migrants' academic achievement in the context of the Mexican war on drugs. Using student location choices across space and over time, we recover individual-level migration paths for elementary school students across all municipalities in Mexico. We find that students who were induced to leave violent areas due to increased violence experience academic gains after relocating to safer areas. Students who migrated from municipalities in the 90th percentile of the violence distribution to municipalities in the 10th percentile experienced improvements of 5.3 percent of a standard deviation in their test scores two years after they migrated. These results appear to be explained by increases in school attendance and improvements in the learning environment after they moved.
Keywords: I24; I25; O15; 330; local violence; migration; educational trajectories